Hubungan Durasi Penggunaan Gadget terhadap Personal Sosial pada Anak Usia 1-6 Tahun di Kota Depok - Purwadi, Hendro; Fitriyani, Lia (MAHESA : Malahayati Health Student Journal, 2023)
ABSTRACT Some of the countries with the largest use of the first gadget include China with 574.2 million, USA with 184.2 million, India with 167.9 million, Russia with 58.2 million, Japan with 57.4 million, Indonesia with 52.2 million and Brazil with 48.6 million. To know the relationship between the duration of gadget use and social personal in children aged 1-6 years in Depok City. This study used an analytical survey method with a cross-sectional design. The population in this study were children aged 1-6 years in Depok City with a total of 166,773 children. The sample in this study were 150 children. This sampling technique uses probability sampling. The data analysis used was univariate (frequency distribution) and bivariate (chi square test). 69.3% (104 children) of children aged 1-6 years using gadgets > 1 hour per day and 52.7% (79 children) being in the low category of children aged 1-6 years. The results of the chi square test show that there is a relationship between the duration of gadget use and personal social behavior in children aged 1-6 years in Depok City (P Value = 0.000). There is a relationship between the duration of gadget use and personal social behavior in children aged 1-6 years in Depok City. Keywords: Duration, Gadget, Personal Social  ABSTRAK Beberapa Negara yang penggunaan gadget terbesar yang pertama diantaranya Cina sebanyak 574.2 juta, USA sebanyak 184,2 juta, India sebanyak 167,9 juta, Rusia sebanyak 58,2 juta, Jepang sebanyak 57,4 juta, Indonesia sebanyak 52,2 juta dan Brazil sebanyak 48,6 juta. Diketahuinya hubungan durasi penggunaan gadget terhadap personal sosial pada anak usia 1-6 tahun di Kota Depok. Penelitian  ini menggunakan metode survei analitik dengan desain cross-sectional.  Populasi  dalam penelitian ini adalah anak usia 1-6 tahun di Kota Depok sebanyak 166.773 anak. Sampel dalam penelitian ini adalah 150 anak. Teknik pengambilan sampel ini menggunakan probality sampling. Analisis data yang digunakan adalah analisis univariat (distribusi frekuesin) dan bivariat (uji chi square). Anak usia 1-6 tahun durasi penggunaan gadget > 1 jam perhari sebesar 69,3% (104 anak) dan personal social anak usia 1-6 tahun dalam kategori rendah sebesar 52,7% (79 anak). Hasil uji chi square ada hubungan durasi penggunaan gadget terhadap personal social pada anak usia 1-6 tahun di Kota Depok (P Value = 0,000). Ada hubungan durasi penggunaan gadget terhadap personal social pada anak usia 1-6 tahun di Kota Depok. Kata Kunci: Durasi, Gadget, Personal Sosial